RAISE - Um metamodelo de informação de rastreabilidade - Pedro Lopes da Rocha Leal Junior (2011)
Traceability, the ability to describe and follow the life of software elements, was conceived as a solution of the fundamental problems of software development process: ensuring software compliance with its requirements. Even though it\\\'s already been decades of studies, Traceability is still rarely defined and used. Initially, the Traceability study focused on the Requirements Engineering with the name of Requirements Traceability, but in recent years, Traceability has also gained importance for researchers from other areas of Software Engineering. This diversity of Traceability initiatives in research has brought as a result that different research groups would establish different goals and granularity to their research. As these researchers tend to be part of communities where there is little communication, advances in Traceability are unbalanced. Different methods used to keep the information for Traceability have been created, but none of them has yet been able to make it be used systematically. These methods use models to represent the Traceability information. There are also many proposals for different models, but the establishment of a single model for Traceability has not been possible due to the dependence of the organizational context where the model is used. The syntax and semantics of information models of Traceability can be defined through a metamodel for Traceability Information. This metamodel should be used in creating a model of Traceability Information for each organization or project. The aim of this paper is to present the Metamodel RAISE, which is a Traceability Information Metamodel that allows the recording of the context where Information Traceability is inserted. RAISE contextualizes Traceability through elements of the process of software development of a specified organization. We believe this will allow records of Traceability to be used based on their context of usage, as indicated by Pohl.